2004
DOI: 10.1093/eurheartj/ehi069
|View full text |Cite
|
Sign up to set email alerts
|

Comparative assessment of right, left, and biventricular pacing in patients with permanent atrial fibrillation

Abstract: Rhythm regularization achieved with AV-junction ablation improved quality of life and exercise capacity with all modes of pacing. LV and BiV pacing provided modest or no additional favourable effect compared with RV pacing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
67
1
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(73 citation statements)
references
References 25 publications
2
67
1
3
Order By: Relevance
“…Furthermore, the deleterious effect of RV pacing was mitigated by the use of biventricular pacing. Around the same time, Brignole et al randomized 56 patients with permanent AF who were undergoing AVJA and implantation of a biventricular pacing system to undergo either RV‐ or LV‐only pacing 6. Three months later, the patients were crossed over to the other arm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the deleterious effect of RV pacing was mitigated by the use of biventricular pacing. Around the same time, Brignole et al randomized 56 patients with permanent AF who were undergoing AVJA and implantation of a biventricular pacing system to undergo either RV‐ or LV‐only pacing 6. Three months later, the patients were crossed over to the other arm.…”
Section: Discussionmentioning
confidence: 99%
“…Although right ventricular (RV) pacing has been most commonly used, concerns have been raised about the deleterious impact of RV pacing on clinical outcomes; in some patients, clinical deterioration can occur within months of pacemaker implantation 3. Thus, several investigators have explored the role of biventricular pacing in this patient population 4, 5, 6, 7, 8. However, these studies have produced conflicting results, likely in part because of the relatively few patients enrolled and variability in follow‐up duration.…”
mentioning
confidence: 99%
“…Nevertheless, results of other studies concerning quality of life are very variable and do not always follow the above assumption. Some studies reported only slight improvement in quality of life in both groups observed, but with no signifi cant difference between them (27). It is also noteworthy that the observation periods in the pilot phase of our study were short (6+6 months).…”
Section: Discussionmentioning
confidence: 47%
“…Few randomized trials have been done in order to assess the efficacy of CRT in AF patients [58][59][60]. The MUSTIC trial showed good one-year results of biventricular pacing in patients with severe HF and major intraventricular conduction disturbances with either SR or AF [58].…”
Section: Heart Failure: Cardiac Resynchronization Therapy In Afmentioning
confidence: 99%
“…Furthermore, the global effective 'CRT-dose' may be markedly reduced compared with atrial synchronous rhythm with a short AV interval achieved during SR, since the number of effective biventricular captured beats are reduced. Moreover, in AF patients, spontaneous ventricular rate tends to overdrive biventricular pacing rates during exertion, determining a further reduction of paced beats precisely when patients are most in need of biventricular capture, and thus greatly limiting functional capacity [60,61]. Another problem is the possible negative impact on prognosis of negative chronotropic therapy in achieving adequate rate control.…”
Section: Heart Failure: Cardiac Resynchronization Therapy In Afmentioning
confidence: 99%